Digital Platform Capability and Strategic Agility: Uncovering Strategies to Strengthen Indonesian F&B SMEs Competitiveness - Henryanto, Aria Ganna; Hanifah, Haniruzila; Kaihatu, Thomas Stefanus; Hardjono, Retno Kusumastuti; Cahyadin, Malik; Hartono, Wendra (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The Indonesian food and beverages (F&B) SME sector was a major contributor to the economy but faces challenges such as intense market competition and limited digital adoption. Despite the strong potential of the digital market, only a small proportion of SMEs were integrated into digital ecosystems. Understanding how digital platform capabilities (DPC) and strategic agility (SA) influence competitiveness was crucial in this dynamic environment.Purpose: This study examines the effect of digital platform capability on the competitiveness of small and medium-sized enterprises (SMEs), considering the mediating role of strategic agility and the moderating role of competitive intensity within Indonesia's food and beverage (F&B) sector.Design/methodology/approach: This study was rooted in the philosophy of positivism, with a deductive design. Data were collected from 142 Indonesian F&B SMEs through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The variables included DPC (independent), SA (mediator), SMEs competitiveness (dependent), and competitive intensity (moderator).Findings/Result: SA mediates the relationship between DPC and competitiveness, which in turn increases strategic agility and the competitiveness of SMEs. The overall model explains 42% of the variance in SMEs competitiveness, which is moderately high, and competitive intensity negatively moderates the SA-competitiveness link, making agility less effective in high competition.Conclusion: Digital platform capabilities are essential for improving SME competitiveness, particularly when they are combined with strategic agility. However, the effectiveness of agility depends on market conditions; high competitive intensity may reduce its benefits. SMEs must balance agility with operational stability, and policymakers should support digital infrastructure and capability-building initiatives.Originality/value (State of the art): This study contributes to the literature by integrating resource orchestration theory with digital transformation and agility concepts in the context of emerging markets. It empirically demonstrates the mediating role of agility and the contextual influence of competitive intensity, offering nuanced insights for both theory development and SME digitalization strategies in volatile environments. Keywords: SMEs competitiveness, digital platform capability, strategic agility, competitive intensity